Intercellular translocation of molecules via plasmodesmata in the multiseriate filamentous brown alga, Halopteris congesta (Sphacelariales, Phaeophyceae). Issue 2 (3rd January 2017) - Nagasato, Chikako; Tanaka, Atsuko; Ito, Toshiaki; Katsaros, Christos; Motomura, Taizo
Abstract : Despite the high number of studies on the fine structure of brown algal cells, only limited information is available on the intercelluar transportation of molecules via plasmodesmata in brown algae. In this study, plasmodesmatal permeability of Halopteris congesta was examined by observing the translocation of microinjected fluorescent tracers of different molecular sizes. The tip region of H. congesta consists of a cylindrical apical cell, while the basal region is multiseriate. Fluorescein isothiocyanate‐dextran (FD; 3, 10, and 20 kDa) and recombinant green fluorescent protein (27 kDa) were injected into the apical cell and were observed to diffuse into the neighboring cells. FD of 40 kDa was detected only in the injected apical cell. The plasmodesmatal size exclusion limit was considered to be more than 20 kDa and less than 40 kDa. The extent of translocation of 3 and 10 kDa FD from the apical to neighboring cells 2 h postinjection was estimated based on the fluorescence intensity. It was suggested that the diffusing capacity of plasmodesmata varied according to molecular size. In order to examine acropetal and/or basipetal direction of molecular movement, 3 and 10 kDa FD were injected into the third cell from the apical cell. Successive observations indicated that the diffusion of fluorescence in the acropetal direction took longer than that in the basipetal direction. No ultrastructural difference in plasmodesmata was noted among the cross walls.